Effectiveness of Acupuncture for Lateral Epicondylitis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Yumei Zhou; Yuebao Guo; Rui Zhou; Ping Wu; Fanrong Liang; Zhuoxin Yang (Pain Research and Management)
Objective. This study aimed at assessing the clinical effectiveness of acupuncture for lateral epicondylitis (LE). Methods. The following databases were systematically searched: China National Knowledge Infrastructure, Chinese Science and Technology Periodical Database, Wan Fang database, Chinese Biomedicine Literature, PubMed, EMBASE, and Cochrane Library from inception to May 2019. Randomized controlled trials (RCTs) meeting the inclusion criteria were included. RevMan 5.3 software was used to conduct meta-analyses. The study quality was evaluated with the Cochrane risk of bias. Results. Ten RCTs involving 796 individuals were included in this meta-analysis. Three studies reported randomized methods with a specific description. For the analyses of the clinical efficacy rate, acupuncture outperformed sham acupuncture (two RCTs, n = 130, P=0.15), medicine therapy (two RCTs, n = 124, P=0.02), and blocking therapy (four RCTs, n = 427, P=0.0001). For the analyses of the visual analog scale, acupuncture outperformed sham acupuncture (two RCTs, n = 92, P=0.18), medicine therapy (two RCTs, n = 144, P<0.00001), and blocking therapy (two RCTs, n = 132, P=0.03). The subgroup analyses comparing acupuncture with sham acupuncture therapy revealed heterogeneities. The follow-up information and adverse reactions were not analyzed because of the insufficient number of studies. Conclusions. Acupuncture appears to be superior to drug or blocking therapy or sham acupuncture therapy for LE. However, considering the low quality of the available trials, further large-scale RCTs with a low risk of bias are needed in the future.